Description of a New Species Hepatozoon quagliattus sp. nov. (Apicomplexa: Adeleorina: Hepatozoidae), infecting the Sleep Snake, Dipsas mikanii (Squamata: Colubridae: Dipsadinae) from Goiás State, Brazil - Úngari, Letícia Pereira [UNESP]; Netherlands, Edward C.; de Alcantara, Edna Paulino [UNESP]; Emmerich, Enzo [UNESP]; da Silva, Reinaldo José [UNESP]; O´Dwyer, Lucia Helena [UNESP] (Springer Nature, 2021)
Purpose: Species of Hepatozoon Miller, 1908 (Hepatozoidae) are blood protozoans with a cosmopolitan distribution and are reported to parasitize a range of vertebrate hosts including mammals, birds, reptiles, and amphibians. The present study aimed to describe a new species of Hepatozoon (Apicomplexa: Adeleorina: Hepatozoidae) found infecting the sleep snake Dipsas mikanii (Schlegel, 1837) (Squamata: Colubridae: Dipsadinae). Methods: The snake was collected in 2017 at the municipality of Britânia, Goiás State, Brazil. Blood smears were made in order to find blood gametocytes and PCR was performed targeting the 18S rRNA gene. Results: Microscopy screening of blood smears revealed the presence of intraerythrocytic gamont stages of Hepatozoon sp. in the peripheral blood with a parasitemia of 0.25%. Furthermore, meronts and monozoic cysts were observed in histological sections of the liver from the infected individual. The interspecific divergence of 18S rRNA sequences fragments isolated from D. mikanii had differences (2.39–11.3%) as compared to other sequences of species of Hepatozoon from snakes. Conclusions: Based on morphological and molecular data, a new species of Hepatozoon infecting D. mikanii from Brazil is described.
Keywords: 18S rRNA; Haemogregarine; Hemoparasite; PCR; Reptile; Snake